The highly efficient cathode of framework structural Fe2O3/Mn2O3 in passive direct methanol fuel cells. (1st February 2020) - Fang, Yuan; Zhang, Tingting; Wang, Yonghui; Chen, Yuanzhen; Liu, Yan; Wu, Wenling; Zhu, Jianfeng
Graphical abstract: Highlights: A high-efficient and cost-effective direct methanol fuel cell is proposed. The peak power density is higher than both electrodes with noble catalysts. Faradic efficiency of 85.1% and energy efficiency of 42.2% were obtained. Enhanced O2 adsorption and transfer capacity were obtained on cathode. The half-wave potential of Fe2 O3 /Mn2 O3 outperforms commercial Pt/C. Abstract: The development of power density and energy conversion efficiency of direct methanol fuel cells (DMFCs) is of great significance. This study presents a high-efficiency passive DMFC consisting of hetero-structured Fe2 O3 /Mn2 O3 as the cathode catalyst, PtRu/C as the anode catalyst and polymer fiber membrane (PFM) as the electrolyte membrane. The peak power densities reached up to 60.6, 121.2 and 186.6 mW cm −2 at 20, 50 and 70 °C, respectively, which was approximately 2.7 times greater than a normal cell composed of commercialized Nafion membrane and Pt/C cathode catalyst at 20 °C. Faradic efficiency of 85.1% and energy efficiency exceeding 42.2% were obtained. Herein, Fe2 O3 /Mn2 O3 displays framework structure with edge lengths of 1 to 2 μm homogeneous micro-cubes. A synergistic effect between α-Fe2 O3 and α-Mn2 O3 matrix in Fe2 O3 /Mn2 O3 significantly enhances its oxygen reduction reaction (ORR) catalyzed activity. α-Fe2 O3 with abundant oxygen vacancies could store and release O2 through the transformation of Fe 3+ /Fe 2+ redox couple. The three-dimensional mesoporous channel structure of Fe2 O3 /Mn2 O3 could act as effective mass transfer reactors, in which O2 and electrolyte is uninhibited accessed to active sites. On the other hand, numerous heterogeneous interfaces can boost electron transfer efficiency, which is investigated using the electron transfer number, narrow band gap and lower charge transfer resistance. The output performance and the energy conversion efficiency of DMFCs is considerably improved through boosting oxygen and charge transfer capability in cathode. Overall, our result provides a promising strategy to fabricate high-efficient and cost-effective fuel cells for the enhanced power conversion.